2000
DOI: 10.1016/s0962-8924(00)01851-1
|View full text |Cite
|
Sign up to set email alerts
|

Cellular organelles: how lipids get there, and back

Abstract: 104 Siegel, M.D. et al. (1995) Activation of the interleukin-5 promoter by cAMP in murine EL-4 cells requires the GATA-3 and CLE0 elements. J. Biol. Chem. 270, 24548-24555 105 Ranganath, S. et al. (1998) Richter, A. et al. (1999) Instruction for cytokine expression in T helper lymphocytes in relation to proliferation and cell cycle progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Although lipid rafts are considered as ubiquitous constituents of plasma membrane or Golgi, which is in agreement with the enrichment of lipid rafts in these loci, recent studies indicated that lipid rafts are similarly formed at the subcellular membranes with relatively low concentrations of cholesterol and glycosphingolipids (van Meer and van Genderen, 1994; van Meer, 2000). For example, it is known that mitochondrial membranes contain lipid rafts that are remodeled and redistributed during apoptotic and immune reaction, thus initiating cell death signals derived from mitochondria (Malorni et al, 2007).…”
Section: 1 Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…Although lipid rafts are considered as ubiquitous constituents of plasma membrane or Golgi, which is in agreement with the enrichment of lipid rafts in these loci, recent studies indicated that lipid rafts are similarly formed at the subcellular membranes with relatively low concentrations of cholesterol and glycosphingolipids (van Meer and van Genderen, 1994; van Meer, 2000). For example, it is known that mitochondrial membranes contain lipid rafts that are remodeled and redistributed during apoptotic and immune reaction, thus initiating cell death signals derived from mitochondria (Malorni et al, 2007).…”
Section: 1 Introductionmentioning
confidence: 63%
“…Overexpression of sigma-1 receptors increases ganglioside GD1a in plasma membrane rafts, the endproduct of the ganglioside synthesis, but decreases less-glycosylated precursors of GD1a such as GM1 and GM2 (Takebayashi et al, 2004b). Because the biosynthesis of glycopshingolipids downstream of ceramides is entirely processed at Golgi (van Meer, 2000), this finding suggests the sigma-1 receptor accelerating glycosylation of gangliosides at the Golgi apparatus. The reconstitution of plasma membrane rafts caused by sigma-1 receptors therefore promotes a significant alteration in signal transduction triggered by receptors of trophic factors as mentioned below.…”
Section: 7 Roles Of Sigma-1 Receptors In Subcellular Distribution mentioning
confidence: 96%
“…Our observation that the parasite's food vacuolar membrane is more susceptible to lipid peroxidation than the plasma membranes of the parasite or host erythrocyte is a reflection of the different contents of polyunsaturated fatty acids, which is usually higher in vacuolar membranes (39). This explains lysis of the food vacuole under conditions where the parasite plasma membrane and the erythrocyte plasma membrane remain intact and are still able to contain fluorescent dyes (Figs.…”
Section: Discussionmentioning
confidence: 85%
“…Though the ER synthesizes almost all types of lipids or their precursors including cholesterols and sphingolipids, those lipids are actively transported by vesicular and nonvesicular systems to the Golgi apparatus ( van Meer, 2000; van Meer and van Genderen, 1994). In contrast to the growing number of MAM-enriched proteins, the lipid compositions of the MAM are largely unknown.…”
Section: Lipid Components Of the Mammentioning
confidence: 99%